(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The presented work presents the concept of simultaneous operations, a review of domestic and foreign literature on the problems of performing simultaneous operations in gynecology - issues of terminology, classification, features of performing combined operations when combining gynecological diseases with another surgical pathology.